Partial Empty Sella Syndrome: A Case Report and Review - Aruna, P. (Springer India, 2013)
Empty sella syndrome is a damaged pituitary gland. Either the gland has shrunk or has been crushed and flattened making it look like an empty sella on MRI scan. The reported prevalence of primary empty sella in general population is 8–35 %. The incidence is more in females, the ratio being 5:1. It is generally found in middle aged women who are obese and hypertensive.